The influences of mental health and spiritual intelligence towards well-being and academic performance - Muhammad Salehan Alhafiz, Mat Wajar; Rohana, Hamzah; Ahmad Muhaimin, Mohamad; Christina, Andin (UMP Press, 2022)
This paper presents an insight on the effect of mental health and spiritual intelligence on the happiness and academic performance among undergraduate students at Universiti Malaysia Pahang (UMP). The study had been conducted using quantitative method. A set of questionnaire had been distributed to 460 respondents randomly and selected from a population of 9121 UMP undergraduate students. In prior, the instrument had been checked for its validity and reliability. Results indicate majority of the respondents had achieved high level of mental health, spiritual intelligence and happiness. The correlation analysis revealed that mental health and spiritual intelligence had a significant positive effect on happiness and academic performance. The regression analysis however had shown that happiness had no significant mediation effect on the relationship between mental health and spiritual intelligence and academic performance. Overall, this study had filled in the literature gap on the level of mental health, spiritual intelligence and happiness among students in the context of Malaysian universities particularly in UMP. The model developed by the researcher can be used as a reference in future studies for further investigate how students’ happiness and academic performance can be enhanced through their mental health and spiritual intelligence.